Two new feather mites of the genus Calcealges Gaud, 1952 (Acari: Trouessartiidae) from antbirds (Passeriformes: Thamnophilidae) in Brazil - Hernandes, Fabio A. [UNESP] (Springer, 2015)
Two new feather mites of the genus Calcealges Gaud, 1952 (Acari: Trouessartiidae) are described from antbirds (Passeriformes: Thamnophilidae) in Brazil: Calcealges formicivorae n. sp. from Formicivora grisea (Boddaert) and C. stymphalornithi n. sp. from Stymphalornis acutirostris Bornschein, Reinert &Teixeira. Calcealges formicivorae n. sp. differs from C. trinidadensis Orwig by having, in both sexes, the inner margin of the humeral shields deeply incised and, in females, setae d2 reaching only to the level of trochanters III. Calcealges stymphalornithi n. sp. differs from C. novimundus Orwig, 1968 by having in both sexes the posterolateral areas of the prodorsal shield with longitudinal and oblique striae; males also have the central area of hysteronotal shield without ornamentation and relatively shorter setae d2.